Benefits of Water Aerobic Exercise on Mental Health Outcomes in Severe Mental Illness: The Effects of Sex - Marina Verdaguer-Rodríguez; Josep Oriol Comas; Francesc Garreta; Berta Garcia; Josep Maria Haro; Belen Ribas; Rosana Romero; Laura Nicolau; Bienvenido Mateo; Sandra Marcos; Laura Bassolas; Sonia Vilamala; et al. (Women)
Physical activity is recognized for its physical and mental health benefits, including reducing sedentary behavior and improving mood, anxiety, and self-esteem. Individuals with severe mental illness tend to be more sedentary, contributing to poorer health outcomes. Water aerobic exercise has shown promise in improving physical and mental health, but sex differences in response to such interventions remain underexplored. This study investigates the effects of a water aerobic exercise intervention on 74 individuals with severe mental illness, focusing on sex differences. Participants engaged in a 45–60 session, once a week for 6 months. Assessments were conducted before and after the intervention and included measures of clinical, functioning, quality of life, and sedentary behavior outcomes. Both men and women significantly reduced sedentary behavior. Men showed significant improvements in self-stigma, functioning, and general quality of life. In contrast, women demonstrated significant improvements in self-esteem. These findings suggest that water aerobic exercise may be effective in reducing sedentary behavior and improving mental health outcomes in individuals with severe mental illness. However, the benefits appear to differ by sex. These results underscore the importance of sex-tailored physical activity interventions in mental health care.